UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPA MELALUI MODEL PEMBELAJARAN EVERYONE IS TEACHER HERE PADA SISWA KELAS III SDN 25 CAROCOK ANAU - Rosa Anita (JURNAL MANAJEMEN PENDIDIKAN, 2018)
ABSTRACTBased on the learning outcomes of Class III students at SDN 25 Carocok Anau in science subjects it was found that student learning outcomes in science subjects were still very low. The average student learning outcomes are still under the KKM. The purpose of this study was to describe and obtain information about efforts to improve student learning outcomes in science subjects through the Everyone Is Teacher Learning Model Here in Class III SDN 25 Carocok Anau. This research is a classroom action research. The procedure of research in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 31 Class III students at SDN 25 Carocok Anau. Research data was collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of the research and discussion that have been put forward, it can be concluded that the Everyone Is Teacher Here Learning Model can improve student learning outcomes in science subjects at SDN 25 Carocok Anau. Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle are 51.10 (Enough) increasing to 85.13 (good) with an increase of 34.03%.